Rapid mobilization of membrane lipids in wheat leaf sheaths during incompatible interactions with Hessian fly - Zhu, Lieceng; Liu, Xuming; Wang, Haiyan; Khajuria, Chitvan; Reese, John C.; Whitworth, R. Jeffery; Welti, Ruth; Chen, Ming-Shun (My University, 2012)
Hessian fly (HF) is a biotrophic insect that interacts with wheat on a gene-for-gene basis. We profiled changes in membrane lipids in two isogenic wheat lines: a susceptible line and its backcrossed offspring containing the resistance gene H13. Our results revealed a 32 to 45% reduction in total concentrations of 129 lipid species in resistant plants during incompatible interactions within 24 h after HF attack. A smaller and delayed response was observed in susceptible plants during compatible interactions. Microarray and real-time polymerase chain reaction analyses of 168 lipid-metabolism-related transcripts revealed that the abundance of many of these transcripts increased rapidly in resistant plants after HF attack but did not change in susceptible plants. In association with the rapid mobilization of membrane lipids, the concentrations of some fatty acids and 12-oxo-phytodienoic acid (OPDA) increased specifically in resistant plants. Exogenous application of OPDA increased mortality of HF larvae significantly. Collectively, our data, along with previously published results, indicate that the lipids were mobilized through lipolysis, producing free fatty acids, which were likely further converted into oxylipins and other defense molecules. Our results suggest that rapid mobilization of membrane lipids constitutes an important step for wheat to defend against HF attack.
Citation: Zhu, Lieceng, Xuming Liu, Haiyan Wang, Chitvan Khajuria, John C. Reese, R. Jeff Whitworth, Ruth Welti, and Ming-Shun Chen. 2012. “Rapid Mobilization of Membrane Lipids in Wheat Leaf Sheaths During Incompatible Interactions with Hessian Fly.” Molecular Plant-Microbe Interactions 25 (7): 920–30. https://doi.org/10.1094/MPMI-01-12-0022-R.
Keywords: Hessian fly; Wheat; Rapid mobilization of membrane lipids